Defining Plagiarism: A Literature Review - Akbar Akbar (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
Plagiarism has repeatedly occurred in Indonesia, resulting from focusing on such academic misbehavior as a “central issue” in Indonesian higher education. One of the issues of addressing plagiarism in higher education is that there is a confusion of defining plagiarism. It seems that Indonesian academicians had different perception when defining plagiarism. This article aims at exploring the issue of plagiarism by helping define plagiarism to address confusion among Indonesian academics. This article applies literature review by first finding relevant articles after identifying databases for literature searching. After the collection of required articles for review, the articles were synthesized before presenting the findings. This study has explored the definition of plagiarism in the context of higher education. This research found that plagiarism is defined in the relation of criminal acts. The huge numbers of discursive features used position plagiaristic acts as an illegal deed. This study also found that cultural backgrounds and exposure to plagiarism were influential in defining plagiarism.